Sikap Memidana yang Berorientasi pada Tujuan Pemidanaan - Marcus Priyo Gunarto (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
Punitive attitudes of law enforcers in some criminal cases seem not to benefit the convict, as it does not support the main objective of the criminal justice system. This is because of the absence of binding direction which guides judges in making judgments. In order to benefit the convict, criminal law should formulate a binding direction as well as individualizing punishment which bind all the criminal court. Moreover, there should also be a common understanding among law enforcers that punitive attitude should be balanced with curing attitude. Therefore, physical, substantial and cultural synchronization are needed. The physical synchronization can be conducted through synergy among law enforcers as part of the criminal justice system. The substantial synchronization can be realized through the availability of common understanding among law enforces.